Microwave engineering handbook - Carpentier, Michel Henri; Smith, Bradford L. (Chapman & Hall, 1992)
The Microwave Engineering Handbook provides the only complete reference available on microwave engineering. The three volumes of the handbook cover the entire field of microwave engineering, from basic components to system design. All entries in the handbook are written by experts in the area, bringing together an unrivalled collection of expertise on microwave technology. Volume 3: Microwave systems and applications provides a thorough introduction to the principal applications of microwave technology. Telecommunication, broadcasting, detection and ranging and scientific and industrial applications are covered with appendices on microwave measurement and frequency allocation. This volume shows the range of current and developing applications for microwave technology and will enable readers to appreciate the variety of applications and the requirements for the various system types.